2004
DOI: 10.1124/jpet.104.070334
|View full text |Cite
|
Sign up to set email alerts
|

Serofendic Acid, a Sulfur-Containing Diterpenoid Derived from Fetal Calf Serum, Attenuates Reactive Oxygen Species-Induced Oxidative Stress in Cultured Striatal Neurons

Abstract: We previously identified a novel endogenous substance, serofendic acid, from a lipophilic extract of fetal calf serum. Serofendic acid protects cultured cortical neurons against the cytotoxicity of glutamate and nitric oxide. Here, we reported the protective effect of serofendic acid on reactive oxygen speciesinduced oxidative stress using primary rat striatal cultures. In addition, we compared the neuroprotective effect and the radical-scavenging activity of serofendic acid with those of dimethyl sulfoxide (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The biosynthesis or the metabolism of SFA is unknown at present. Previous studies in vitro indicated that SFA has neuroprotective effects, as evidenced by the prevention of acute glutamate neurotoxicity in cultured cortical neurons (21) and the attenuation of ROS-induced oxidative stress in cultured striatal neurons (22). Suppression of intracellular ROS generation might constitute an important mechanism of the neuroprotective actions of SFA, because the compound exhibits hydroxyl radical-scavenging activity in electron spin resonance analysis (19 body of evidence supports the concept that the inhibition of MPTP is an effective and promising strategy to prevent ischemia/reperfusion injury of the heart (3,6,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…The biosynthesis or the metabolism of SFA is unknown at present. Previous studies in vitro indicated that SFA has neuroprotective effects, as evidenced by the prevention of acute glutamate neurotoxicity in cultured cortical neurons (21) and the attenuation of ROS-induced oxidative stress in cultured striatal neurons (22). Suppression of intracellular ROS generation might constitute an important mechanism of the neuroprotective actions of SFA, because the compound exhibits hydroxyl radical-scavenging activity in electron spin resonance analysis (19 body of evidence supports the concept that the inhibition of MPTP is an effective and promising strategy to prevent ischemia/reperfusion injury of the heart (3,6,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…The atisane diterpene serofendic acid (82), derived from the fetal calf serum and structurally characterized by a sulfur group that is in part responsible for its activity, prevented oxidative damage from paraquat, hydrogen peroxide and nitric oxide in primary neuronal cultures of cortical and striatal rats. Its beneficial effects may be partly due to ROS scavenging and enhancement of endogenous antioxidants [70,71]. Concerning fungi-derived terpenes, the labdane diterpenes 19-hydroxylabda-8(17)-en-16,15-olide (83); 3ß,19-dihydroxylabda-8(17),11E-dien-16,15-olide (84); 13-epi-3ß,19-dihydroxylabda-8(17),11E-dien-16,15-olide (87); 19-hydroxylabda-8(17),13-dien-16,15-olide (88) and 14-deoxy-11,12-didehydroandrographolide (89), obtained from the fruiting body of the parasitic fungus Antrodia camphorata Wu, Ryvarden & Chang appear to be effective antioxidants against amyloid ß-peptide 25-35 in primary cultures of cortical neurons of rats, suggesting that these diterpenes could be promising candidates for drugs preventing oxidative stress occurring in Alzheimer´s disease [72].…”
Section: Neuroprotectionmentioning
confidence: 99%
“…As neurological disorders and neurodegenerative diseases, such as a stroke, Alzheimer's disease, and Parkinson's disease tend to become more frequent, the role of neuroprotective agents becomes more important. Bilobalide and ginkgolide B (sesquiterpene lactone), cannabidiol and delta-9-tetrahydrocannabinol (diterpene), catalpol (monoterpene), serofendic acid (diterpene), and lycopene and crocetin (carotenoid) have shown various protective effects against ischemic and glutamatergic neurotoxicity, 6-hydroxydopamine toxicity, oxidative stress, and so on, both in cellular systems in vitro and animal model systems in vivo (Defeudis, 2002;Logani et al, 2000;Jackson et al, 2005;Lastres-Becker et al, 2005;Li et al, 2004;Osakada et al, 2004;Hsiao et al, 2004;Ahmad et al, 2005). Although neuroprotective activity of various terpenoids with varying effectiveness and action mechanisms have been reported as listed above, it is hard to find studies that compare different terpenoids for neuroprotective activity with reference to their structure.…”
Section: Introductionmentioning
confidence: 99%